DVD/Blu-ray. Issue 1 (1st March 2019) - Amaral, Evan; Colson, Catherine Traci; Johnson, Matt; Spillane, Ashley R.; Watkins, Karl; Wiener, Adam
Only Angels Have Wings (1939) USA Director Howard Hawks Runtime 121 minutes Blu-ray USA, 2016 Distributed by The Criterion Collection (region A/1)Moonrise (1948) USA Director Frank Borzage Runtime 90 minutes Blu-ray USA, 2018 Distributed by The Criterion Collection (region A/1)Song to Song (2017) USA Director Terrence Malick Runtime 129 minutes DVD USA, 2017 Distributed by Broad Green Pictures (region 1)Graduation (2016) Romania Director Cristian Mungiu Runtime 127 minutes Blu-ray USA, 2016 Distributed by The Criterion Collection (region A/1)A Dark Intimacy Between Love and Money Fox and His Friends (1975) Germany Director Rainer Werner Fassbinder Runtime 124 minutes DVD USA, 2015 Distributed by The Criterion Collection (region A/1)La Poison (1951) USA Director Sacha Guitry Runtime 85 minutes Blu-ray USA, 2017 Distributed by The Criterion Collection (region A/1)